Value Added Eco Enzyme Sebagai Sabun Antiseptik - Poppy Nurmayanti M; Yuana Nurulita; Jeni Wardi; Annisa Wulandari; Eka Lestari; Nesya Billa Sausan; Meisy Zahrati Afifah; Meisy Dwi Intan Sari; Niko Andriansyah; Rahmita Khairani Asrar; Yusma Dani; Eliza Khoirunisa; Rialdy (Universitas Lancang Kuning, 2022)
The purpose of community service is to educate the public in processing eco enzymes into products that have added value, as antiseptic soap. This activity was carried out as an effort to support the government's program in maintaining health through the movement of washing hands with soap. The activities method is training and mentoring carried out at the Bank Sampah Agrowisata, Rumbai District, Pekanbaru City. This activity includes two stages. First, the team conducted training and assistance in making eco-enzymes from citrun fruit peels, water, and palm sugar. The organic waste fermentation process is carried out for one month. Second, the team provided training and assistance in making antiseptic soap from eco enzyme. The results the effectiveness of antibacteria test at the Chemistry Laboratory FMIPA, Riau University showed that eco-enzyme that has been processed into soap tends to be more effective at killing bacteria than eco-enzyme. These results are expected to improve the community's economy to support zero waste and improve the skills and entrepreneurial of the community.